2019
DOI: 10.1101/542340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein appetite drives macronutrient-related differences in ventral tegmental area neural activity

Abstract: Amino acids are essential for almost all biological processes and many cannot be synthesized de novo. Thus, it is crucial that all animals, including humans, acquire an adequate amount of protein in their diet. Here, we show that rats maintained on a proteinrestricted diet develop a strong preference for protein, relative to carbohydrate. In addition, this preference was associated with increased neural activation in ventral tegmental area while rats were consuming protein. These changes were relatively persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…In these 'forced choice' trials, no difference in cluster number or cluster size was seen, similar to the pattern of results during conditioning in our previous study when only one bottle was available ( Figure 3B, left). These results demonstrate that, in absence of choice and a comparison between the two nutrientcontaining solutions, rats do not differ in their evaluation of each solution, which explains the similar amount of licking (Chiacchierini, et al, 2019;Murphy, et al, 2018).…”
Section: Effect Of Protein Restriction On Lick Microstructurementioning
confidence: 68%
“…In these 'forced choice' trials, no difference in cluster number or cluster size was seen, similar to the pattern of results during conditioning in our previous study when only one bottle was available ( Figure 3B, left). These results demonstrate that, in absence of choice and a comparison between the two nutrientcontaining solutions, rats do not differ in their evaluation of each solution, which explains the similar amount of licking (Chiacchierini, et al, 2019;Murphy, et al, 2018).…”
Section: Effect Of Protein Restriction On Lick Microstructurementioning
confidence: 68%
“…For example, food restriction increases the magnitude of dopamine evoked by food consumption (142,143). A recent study has also shown that VTA dopamine neuronal activity was higher in protein-deficient rats compared to controls when they consumed a preferred protein food rather than carbohydrate (144). Work from both rodents and human neuroimaging studies is consistent in identifying the dorsal striatum as a key region receiving post-oral nutrient sensing (145)(146)(147)(148).…”
Section: A Incentive Saliencementioning
confidence: 89%
“…The use of SCEDs to evaluate the impact of these manipulations can decrease both labor and technical costs due to the use of fewer animals (in addition to the benefits associated with identifying processes that operate at the level of individual organisms). For example, a fiber photometry study measuring calcium influx in response to protein restriction, which requires intracranial injection of viral vectors and surgical insertion of photosensitive fibers for detecting calcium flux, could utilize the same animals under conditions differing in diets of varying protein content rather than utilizing different groups of mice maintained on different diets varying in protein content (e.g., Chiacchierini et al, 2021). Another interesting avenue to leverage available technologies would be to use mice in which the Fgf 21 gene is placed under control of an exogenous compound using inducible gene expression technology (for a review see Das et al, 2016) such that FGF21 production can be turned on and off during periods of protein restriction in the same animal to determine, in a reversible manner, how FGF21 production governs responses to protein restriction.…”
Section: Discussionmentioning
confidence: 99%